A pilot study on pedsql ™ modul impak keluarga among caregivers of children with transfusion dependant thalassaemia in Hospital USM, Malaysia - Othman Tan, Suria Emilia (2013)
Thalassaemia is one of the commonest genetic blood disorders in the world. It is characterized by inadequate globin chain synthesis, leading to ineffective erythropoiesis, severe anaemia and chronic disease in children and adults. A child with thalassaemia requires lifelong regular blood transfusion in order to prolong survival and reduce extramedullary haematopoiesis. As any other chronic illness, thalassaemia does not only affect patient as an individual; it also involves variety of emotional and psychological burden to the parents and family as a whole. Unfortunately, there are very few studies done worldwide to assess parental heelth related quality of life (HRQOL) in transfusion dependant thalassaemia which is the reason why this study is important.